A Discussion on Chongqing Hotpot and Thumb Fight - Wan, Yao; Dechsubha, Thawascha (Technium Social Sciences Journal, 2022)
Abstract. The paper studies the Chongqing hotpot and two general types of lead-in phrases of Chongqing Thumb Fight. This paper mainly discusses the birthplace and maker of Chongqing hotpot and the origin of the two primary lead-in phrases: Good Brothers and Disorderly Chopping Firewood. The results of studying the Chongqing hotpot and two types of lead-in phrases were found as follows: 1. The Yangtze River is the birthplace of the Chongqing hotpot. 2. The trackers and porters working for the wharves along the Yangtze River create the original Chongqing hotpot. 3. Th encircling rivers cultivate the Good Brothers and the mountainous forests stimulate the Disorderly Chopping Firewood.